Heus! Etiam mensas consumimus. Reescriptures de Carme Riera, Miquel de Palol i Tina Vallès. - ARDOLINO, FRANCESCO (Scripta)
The aim of this contribution is to trace an approach to three Catalan literary works from the common nexus of the réécriture of semantics in food scenes. It is not intended to make any attempt at categorization, but these hypertexts will be arranged in sequence according to the degree of relationship, from minor to major, that they have in comparison with their hypotexts. It will begin with the quote that Carme Riera makes to The Guepard, by Tomasi di Lampedusa, and, passing through Miquel de Palol's references to Satyricon, by Petronius, we will arrive at the explicit remake of Italo Calvino's Palomar by Tina Vallès. The hypothesis of this article is that these rewritings respond to a specific form of hypercitation, which, in the Postmoderm literature, is applied to the idea that, given the impossibility of destroying the past, there remains the possibility of revisiting it -or revising it- in an ironic way.